PROFIL KEMAMPUAN INTERAKSI SOSIAL PESERTA DIDIK DENGAN TEMAN SEBAYA DI KELAS VII SMP NEGERI 27 PADANG - Elmayyeti, Elmayyeti; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The problem of this research is based on the phenomenon that is found by the researcher. There are some students who have low self esteem, impolite, rude, likes to brother his friend. These students give bad impact to studentsâ social interaction among them in the classroom. The purpose of this research is to know the form of studentsâ associative and dissociative social interaction with their pairs at SMP Negeri 27 Padang grade VII. This research is a kind of descriptive research. The population of this study was the entire students grade VII (262 student). The populatotion of this study was 76 students and to get the sample the researcher used simple random sampling technique. The instrument of this research was questionnaire. To analiyze the data the researcher used percentage technique. The researchfindings that (1) associative that involve: a) cooperation that can be classified as deficient 59,12%, b) accommodation belongs of the less well with 61,84%, c) assimilation is classified as deficient with 44,73%,. (2)If we see from dissosiative that involve a) competition belongs of the less well with the percentage 59,21%, b) contravenes belongs of the less well with the percentage 51,31%, c) conflicts belong of the less wellwith 60,52%. Based on the result it can be concluded that studentsâ social interaction with their pairs is not good.